Upaya meningkatkan intelegensi melalui pembentukan kepribadian - Dawami, Asep; Rahman, Imas Kania; Indra , Hasbi; Lisnawati, Santi (Ta’dibuna: Jurnal Pendidikan Islam, 2023)
Personality is an identity that stands out in an individual. Individual intelligence in learning and communicating is influenced by a personality that can influence others. This study aims to determine the development of personality formation from an Islamic perspective that can increase intelligence and the factors that influence it. The method used by the author is a literature study with a qualitative descriptive approach. The conclusion in this discussion is that the formation of personality is inseparable from the concept of human nature which is influenced by three important factors, namely: 1) Heredity factors, 2) Environmental factors, and 3) Hidayah factors and provisions from Allah Almighty which are factors of immense grace. The development of a person’s intelligence can be influenced by three factors, namely; 1) Imitation, 2) Trial and error, and 3) Thinking. In the Islamic view, parents and educators should keep away from four factors that can hinder or even damage values. In the Islamic view, parents and educators should keep away from four factors that can inhibit or even damage their personality values, namely: 1) Distance from inferiority, 2) timidity, 3) Spiteful nature (hasad), and 4) Anger Abstrak Kepribadian adalah identitas yang menonjol pada diri individu. Intelegensi individu dalam belajar dan berkomunikasi dipengaruhi oleh kepribadian yang dapat mempengaruhi orang lain. Penelitian ini bertujuan mengetahui perkembangan pembentukan kepribadian dalam perspektif Islam yang dapat meningkatkan intelegensi dan faktor yang mempengaruhinya. Metode yang digunakan penulis adalah studi pustaka dengan pendekatan deskriptif kualitatif. Kesimpulan dalam pembahasan ini bahwa pembentukan kepribadian tidak terlepas dari konsep fitrah manusia yang dipengaruhi oleh tiga faktor penting yaitu: 1) Faktor hereditas, 2) Faktor lingkungan, dan 3) Faktor hidayah dan ketentuan dari Allah Swt. yang merupakan faktor anugerah yang teramat besar. Perkembangan intelegensi seseorang dapat dipengaruhi oleh tiga faktor yaitu; 1) Meniru, 2) Trial and error (coba dan salah), dan 3) Berpikir. Dalam pandangan Islam orang tua dan pendidik harus menjauhkan dari empat faktor yang bisa menghambat bahkan merusak nilai-nilai kepribadiannya yaitu: 1) Menjauhkan dari sifat minder, 2) Sifat penakut, 3) Sifat dengki (hasad), dan 4) Sifat amarah.